Roundtable Conversation on Hannah Arendt, Plurality, and Democracy with Roger Berkowitz, Samantha Hill, Isabelle Santana, Charlotte Albert, Mark Williams, Jr., and Adrian Costa - Project, Campus Plurality (HannahArendt.net, 2018)
This conversation moves from the work of Hannah Arendt to the college campus environment today, and considers several questions: Who should be invited to campuses? Who has the right to speak? Who is empowered when a speaker presents an argument? What does it mean to be uncomfortable?